Pathways and enhanced evaluation system for green low-carbon development across diverse Chinese regions - Li, Wenjie; Hu, Dechao; Xu, Zongqi; Guo, Jie; Liu, Jianan; Zhou, Yuan (Frontiers in Public Health, 2024)
BackgroundRapid economic growth in China has led to significant resource and environmental challenges, particularly in less economically developed regions. This study aims to identify effective strategies for achieving green, low-carbon development in these regions during the economic transition.MethodsWe employed the Fuzzy-Set Qualitative Comparative Analysis (fsQCA) method to scrutinize the impact of economic, demographic, industrial, and technological factors on low-carbon development across a selection of Chinese provinces, including Qinghai, Hunan, Beijing, Shanghai, Tianjin, Hainan, and Chongqing. This approach facilitates a nuanced exploration of the multifaceted determinants of low-carbon progress within the regional contexts of China.ResultsThe study identified three distinct paths to low-carbon development, each with unique prioritization characteristics. These paths are the traditional early low-carbon path, the semi-modernized mid-carbon path, and the post-modernized low-carbon path. Each path offers tailored strategies for less developed regions to enhance their environmental innovation capacity and global competitiveness.ConclusionThis research contributes a novel perspective for regional sustainable development in China by offering tailored low-carbon development strategies for less developed regions. The findings suggest that region-specific strategies, aligned with developmental stages and characteristics, are essential for ensuring balanced economic, social, and environmental development.